Lung histopathological pattern in a survivor with rapidly progressive interstitial lung disease and anti-melanoma differentiation-associated gene 5 antibody-positive clinically amyopathic dermatomyositis. (2016) - Suzuki, Atsushi; Kondoh, Yasuhiro; Taniguchi, Hiroyuki; Tabata, Kazuhiko; Kimura, Tomoki; Kataoka, Kensuke; Ono, Kenzo; Hashisako, Mikiko; Fukuoka, Junya
Abstract: Anti-melanoma differentiation-associated gene 5 (MDA5) antibodies are specific indicators of patients with dermatomyositis, particularly clinically amyopathic dermatomyositis (CADM). CADM is occasionally accompanied by fatal, treatment-resistant, rapidly-progressive interstitial lung disease (RP-ILD). All previous reports showed that histopathological findings in RP-ILD with anti-MDA5 antibody-positive CADM indicated diffuse alveolar damage (DAD). This is the first report describing a non-DAD pattern in RP-ILD with anti-MDA5 antibody-positive CADM, which was improved by immunosuppressive therapy. This case may be a milder clinical phenotype than a typical DAD pattern in RP-ILD with anti-MDA5 antibody-positive CADM.